Strategi Pengembangan Agroindustri Tahu di Desa Tambakagung Puri Mojokerto - Putri, Icha Alifia Yokendy; Mubarokah, Mubarokah; Widayanti, Sri (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The objectives of this study were to identify the process of making tofu, analyze internal and external factors, and formulate a strategy for the development of tofu agro-industry. The methods used include SWOT analysis, IFE and EFE matrix, and data collection through observation, interviews, questionnaires, and documentation. The results of the analysis show that internal strengths include entrepreneurial experience and product quality, while weaknesses include lack of human resources and simple technology. External opportunities include high consumer purchasing power, while threats include unstable raw material prices. The proposed strategies include improving product quality, branding, optimizing strategic locations, and strengthening relationships with stakeholders. This research provides benefits for students, companies, and universities, and suggests an increased role for MSE organizations, workforce training, and investment in waste management technology. By utilizing existing strengths and opportunities, the tofu agro-industry in Tambakagung Village can be developed effectively and sustainably, contributing to the local economy and job creation.